2007
DOI: 10.1097/01.tp.0000296646.17845.12
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Measurement of ABO Antibodies in ABO-Incompatible Living Donor Kidney Transplantation

Abstract: Due to different detection methods, a comparison of anti-A/B antibody (Ab) levels among transplantation centers after living donor ABO-incompatible kidney transplantation is problematic. In the present study, anti-A/B Ab levels were determined prior to, and after, blood group A-to-O kidney transplantation using a recently established semiquantitative flow cytometry-based method, ABO fluorescence-activated cell sorting (ABO-FACS), and compared with standard agglutination titers and indirect antiglobulin testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
2
25
0
2
Order By: Relevance
“…The technique for isoagglutinin measurement was similar in the two hospitals and published in detail previously (17 Valli et al…”
Section: Direct and Indirect Agglutination Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique for isoagglutinin measurement was similar in the two hospitals and published in detail previously (17 Valli et al…”
Section: Direct and Indirect Agglutination Testmentioning
confidence: 99%
“…Rituximab was administered in median 21 days (range [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (27). (iii) It is well known that the broad antibacterial activity of natural occurring Ab is mainly due to IgM Ab with low specificity and polyreactivity to polysaccharides (16,28 The administration of pooled IVIG is believed to have "immunomodulatory" effects on autoimmune and inflammatory diseases.…”
Section: The Effect Of Intravenous Immunoglobulins and Rituximab On Amentioning
confidence: 99%
“…El número de donantes cadavéricos por año no ha cambiado apreciablemente en la últi ma década y los intentos por disminuir esta brecha justi fi can la necesidad de impulsar programas con donante vivo (DV), siendo la principal barrera encontrada en estos la incompati bilidad de grupo sanguíneo ABO (2) . Históricamente, esta incompati bilidad ha sido considerada contraindicación absoluta para trasplante renal (Tx) (3) y cuando era realizado inadverti damente, se observaba la rápi-da y temprana pérdida del injerto, debido a rechazo mediado por anti cuerpos anti grupo sanguíneo (4)(5)(6) . Esto requirió la necesidad de impulsar protocolos consistentes en remover los anti cuerpos anti grupo ABO previos al trasplante renal (7,8) , promoviendo minimizar e individualizar éstas terapias (9,10) .…”
Section: Introductionunclassified
“…For example, the A blood group antigen has higher expression levels than the B blood group antigen. Interestingly, immunohistochemical analysis has revealed that the A2 blood group has the lowest cell surface expression (Pober et al, 1997;Shimmura et al, 2004;Yung et al, 2007); however, data analysis of kidney transplants that has been performed across ABO barriers has not revealed statistically significant differences between the A (donor) →B (recipient) or B (donor) →A (recipient) groups (Squifflet et al, 2004;Sugiyama et al, 2005;Valli et al, 2009). …”
Section: Antibodies Against a And B Blood Groupsmentioning
confidence: 99%